ØªØÙ„ÙŠÙ„ ÙƒØªØ§Ø¨ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠÙ‘Ø© Ù„Ù„ØµÙ‘Ù Ø§Ù„Ø«Ù‘Ø§Ù†ÙŠ Ø¹Ø´Ø± Ù…Ù† Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ø«Ù‘Ø§Ù†ÙˆÙŠÙ‘Ø© Ù„Ø¯ÙƒØªÙˆØ± Ù‡Ø¯Ø§ÙŠØ§Øª - Mariatul Qibtiyah; Isniyatun Niswah; Chusnia Rahmawati (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2021)
The study of Arabic textbooks is considered important because it relates to the content of material contained in the book. The Arabic language textbook for Madrasah Aliyah class XII by Dr. Hidayat was compiled based on the Madrasah Curriculum issued by the minister of religion of the Republic of Indonesia in 2013, which the author made as the object of study in this thesis. While a good Arabic language book can be assessed from the four aspects of the book assessment initiated by the National Education Standards Agency (BSNP), namely aspects of content, presentation, language and graphics. This research is a type of literature research using a qualitative approach. The collection process is carried out with documentation techniques. While, the data analysis that the writer uses in this research is content analysis. The results showed that the Arabic language textbook for Madrasah Aliyah class XII by Dr. Hidayat is suitable to be used as a school textbook, because from the aspect of content feasibility it’s know that the textbook is included in the fairly decent category, in the aspect of presentation feasibility it’s know that the textbook is included in the less appropriate category. Very feasible, and from the aspect of the feasibility of the graphics in this textbook, it’s know that this textbook is included in the category that is quite worthy